Geopolitics and Muslim Countries: Navigating Challenges and Opportunities in Contemporary International Political Dynamics - Yahdi Qolbi; M. Ibnu Ashari. R; Diana; Imaro Sidqi (Faculty of Sharia, IAIN Metro, 2024)
This study aims to analyze the role of Muslim countries in global geopolitics and how they navigate challenges while capitalizing on opportunities amid the international political dynamics in the era of globalization. As the world order undergoes significant shifts, Muslim countries face complex issues such as geopolitical tensions, regional conflicts, major power interventions, and changing strategic alliances. However, they also have opportunities to strengthen their diplomatic and economic positions through international collaboration, investment, and active roles in multilateral organizations. Using a qualitative analysis approach, this research examines foreign policy, diplomatic strategies, and international relations dynamics of Muslim countries, including their role in organizations like the Organization of Islamic Cooperation (OIC) and their relations with major powers like the United States, China, and Russia. The study employs a qualitative analysis approach with a literature review method. Data is sourced from secondary materials such as academic journals, books, policy reports, and articles relevant to the geopolitical issues of Muslim countries. This approach enables the researcher to analyze various foreign policies, diplomatic strategies, and dynamics in international relations. The data is then analyzed using a descriptive-analytical approach to explore the role of Muslim countries in global geopolitics and how they tackle challenges while leveraging opportunities in the era of globalization. The findings indicate that despite significant challenges, Muslim countries possess the potential to act as critical players in global geopolitics if they can optimize available opportunities, such as enhancing economic cooperation and diplomacy based on shared interests.